Channels Ran Through It—The Lawrence Formation at Lone Star Lake, Douglas County, Kansas - Enos, Paul; Jefferson, Robert D.; Goetz, Staci L. (Current Research in Earth Sciences, 2008)
The upper part of the Ireland Sandstone Member of the Lawrence Formation exposed in the spillway of Lone Star Lake, southwest of Lawrence, Kansas, consists of abundant pinstripe-bedded shales and siltstones; thin, lenticular sandstone and siltstone beds; and meter-scale, channel-form sandstone and mudstone lenses. Soft-sediment-deformation structures, including load casts, ball-and-pillow, and pseudonodules are abundant. The lenticular and pinstripe bedding with bipolar paleocurrents suggests tide-influenced deposition. The crosscutting, channel-form deposits are interpreted as tidal channels in an environment with low energy but rapid sedimentation. The depositional environment was a tide-dominated, muddy upper estuary cut by tidal channels. Gravitational instabilities resulting from rapid deposition of sand over saturated mud produced inverse-density gradients that resulted in soft-sediment deformation.